Estudo das proteínas HSP70, SOD e catalase de Angiostrongylus cantonensis em hospedeiros habituais e acidentais - Rosa, Thaise Paím da (2014)
Angiostrongylus cantonensis is a nematode of the Angiostrongylidae family. In humans, they can cause eosinophilic meningitis. Although the parasite have been described in 1935, little is known about the mechanisms of adaptation to its hosts. A. cantonensis owns molecules that help the parasite in the evasion of the host´s immune system, among these are SOD, catalase and HSP70. The main goal of this work was to study the profiles of HSP70, SOD and CAT of L5 produced in different hosts and analyze the diagnostic potential of the extracts. For the obtainment of fifth stage larvae (L5), rats and mice were infeceted with 104 and 50 third stage larvae, respectively, and euthanized after 21 days. The L5 were recovered from the brain of the animals and homogenized in different buffers to obtain the protein extracts. The quantification of the total protein suggests no significant difference between extracts. For the identification of HSP70, it was performed dot blot and Western blot, showing that in both samples HSP70 were present. ELISA assays were used for the quantification of HSP70 and analyze antigen-antibody binding with from individuals with confirmed diagnosis for angiostrongyliasis. L5 from usual hosts were recognized by the sera showing superior titles to the L5 from the accidental hosts. Levels of stress proteins HSP70, SOD (339U versus 0.08U of SOD/mg of protein) and catalase (184.4 versus 75.6 pmol of CAT mg-1 proteins) were higher p<0.05, in A. cantonensis larvae from usual hosts in comparison to the larvae obtained from accidental hosts. These data suggest that the levels of stress proteins may be associated to the adaptation of A. cantonensis to the usual hosts.